Functional nutritional rice: current progresses and future prospects - Duan, Sumei; Ai, Hao; Liu, Shengqin; Zhou, Aifeng; Cao, Yuhong; Huang, Xianzhong (Frontiers in Plant Science, 2024)
More than half of the world's population relies on rice as their staple food for three meals a day. From a dietary perspective, rice can be considered the most important grain in the world. With the continuous improvement of people's living standards, the demand for food has gradually shifted from being full and eating well to being nutritious and healthy. Developing functional nutritional rice has become an important research direction and strategic initiative for developing a major food concept. In this paper, we review the current progress in the breeding of functional nutritional rice and mineral-biofortified rice. This review focuses on the following aspects: (ⅰ) the concept, rice basic structure, nutritional components, and categorization of functional nutritional rice; (ⅱ) genes that have been applied and identified so far, including nutritional functional rice genes, mineral bioenhancement-related genes, and their regulatory mechanisms; (ⅲ) based on the history and technical mainline of rice breeding, research progress in nutritional functional rice using conventional breeding, a combination of conventional breeding and marker-assisted breeding, mutagenesis breeding, genetic engineering technology, and gene editing technology. Based on the current research and industrialization issues, we highlight an outlook of the problems and future developmental directions in nutritional functional rice research.